Nguni fermented foods: working with indigenous knowledge in the Life Sciences: a case study - Hanisi, Nosipho (Rhodes University, Faculty of Education, Department of Education, 2007)
This study examines learning interactions around indigenous ways of knowing associated with fermented grain foods (the making of umqombothi) and the concept of alcoholic fermentation in the Grade 11 Life Sciences curriculum. As an environmental education study it also investigates the cultural significances of the fermented grain food and how learners might make better lifestyle choices. The inclusion of indigenous ways of knowing in the Life Sciences curriculum (FET band) created spaces and opportunities for the use of both knowledge's in sociocultural context and the structured propositions of the learning area in order to construct knowledge. This stimulated learners' understanding of fermentation and also led to a valuing of social context as well as the cultural capital embedded in the indigenous ways of knowing. The study suggests that parental involvement contributed to this valuing of intergenerational ways of knowing. Learners also deliberated how colonial interpretations of Nguni culture and the religious beliefs of Christians had served to marginalise and foster a widening urban rejection of isiXhosa cultural practices related to fermented foods. In their learning and discussion, learners developed new insights and respect for isiXhosa fermentation practices (ukudidiyela) that bring out the food value and nutrition in the grain. The data illustrates that lesson activity that drew on relevant Learning Outcomes and Assessment Standards to integrate Indigenous Knowledge practices in a Life Sciences learning programme, served to enhance learner understanding of alcoholic fermentation. They also document a revaluing of cultural heritage and learners bringing up the problem of alcohol abuse in the community. Curriculum work with Indigenous Knowledge thus not only assisted learners to grasp the science but to use this alongside a valued cultural knowledge capital to deliberate and act on a local concern.
Keywords: Life sciences -- Study and teaching (Secondary) -- South Africa -- Case studies; Environmental education -- South Africa -- Case studies; Fermented foods -- Case studies; Fermentation Indigenous peoples -- Case studies; Nguni (African people) -- Social life and customs; Xhosa (African people) -- Social life and customs; Ethnoscience